Study Protocol effectiveness of a nutritional intervention based on encouraging the consumption of unprocessed and minimally processed foods and the practice of physical activities for appropriate weight gain in overweight, adult, pregnant women: a randomized controlled trial - Daniela Saes Sartorelli; Lívia Castro Crivellenti; Marina Garcia Manochio-Pina; Naiara Franco Baroni; Mariana Rinaldi Carvalho; Rosa Wanda Diez-Garcia; Laércio Joel Franco (BMC, 2020)
Abstract Background Evidence from observational studies suggests that a greater intake of ultra-processed foods during pregnancy is associated with a higher chance of obesity, increased gestational weight gain, and neonatal adiposity. The aim of the present study is to evaluate the effectiveness of a nutritional intervention based on encouraging the consumption of unprocessed and minimally processed foods and the practice of physical activities for appropriate weight gain in overweight, adult, pregnant women. Additionally, the effect of the intervention on pregnancy outcomes, neonatal adiposity, and the child's weight and height will be investigated. Methods This is a two-armed parallel randomized controlled trial that will be conducted at primary health units in Ribeirão Preto, SP, Brazil. Adult pregnant women who are overweight and receiving prenatal care in the public health system will be included. The women will be randomly allocated into control (standard care) or intervention groups. Those enrolled in the intervention group will participate in three individualized nutritional counselling sessions based on encouraging the consumption of unprocessed and minimally processed foods and the practice of physical activities. The recruitment of the participants will be carried out at seven health facilities over 12 months, with a sample of 300 women expected. Maternal anthropometric, sociodemographic, blood pressure, biochemical, and lifestyle data will be obtained at baseline (up to the 16th week of gestation), and during a second assessment (34th to 36th gestational week). The neonate body composition will be estimated after birth, and data on pregnancy outcomes, weight and height of children at 6, 12 and 24 months of age will be further obtained from medical records. Discussion This will be the first randomized controlled trial to test the effectiveness of a nutritional intervention based on encouraging the consumption of unprocessed and minimally processed foods and the practice of physical activities for appropriate weight gain in adult, overweight, pregnant women. Furthermore, the effect of the intervention on pregnancy outcomes, neonatal adiposity and the child's weight and height will be evaluated. Trial registration Registro Brasileiro de Ensaios Clínicos (Rebec) RBR-2w9bhc July 30th 2018 (http://www.ensaiosclinicos.gov.br/rg/?q=RBR-2w9bhc+), and RBR-7yx36h June 4th 2019 (http://www.ensaiosclinicos.gov.br/rg/?q=RBR-7yx36h+0.